RELATIONSHIP OF WRITING LEARNING PROCESSES WITH LANGUAGE ERRORS OF STUDENT EXPOSITION (Research Language Errors in SMAN 4 Tambun Selatan) - Ria Anggari Putri; Miftahulkhairah Anwar; Siti Ansoriyah (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2020)
Abstract:This study aims to find out and explain the interrelationship of the learning process of writing with errors in the exposition of students. The method used is descriptive qualitative method which aims to describe and explain the relevance of the learning process of writing with the errors of the exposition of students. The object of this research is the exposition of class X high school students assisted by questionnaire. The results of this study indicate that the more maximum the process of learning to write, the better the results obtained, and conversely the instant process and teachers who do not maximize teaching in the methods and media used will be increasingly less quality. Keywords: writing, language errors, exposition